MASSA KLASIK SOLITON PERSAMAAN SCHRÖDINGER NONLINEAR - Prayitno, T. B. (BERKALA FISIKA, 2011)
We have calculated classical mass of soliton of nonlinear Schrödinger equation in thecase of (1+1) space-time dimension. The equation describes the propagation of electromagneticwave in combination of dispersive-nonlinear medium. The propagation itself will create a stableelectromagnetic pulse. The first thing that must be done is to calculate analytical solution of onesoliton of nonlinear Schrödinger equation by transforming wave function and continuing byapplying direct integration. The definition of its classical mass is based on classical field theory bybeginning the construction of Lagrangian density and continuing Hamiltonian density of thatnonlinear equation. The Lagrangian density is obtained by trial function relating by Euler Lagrange that creates appropriate nonlinear Schrödinger equation.Keywords:Soliton,Nonlinear Schrödinger.